Bacterial coinfection in critically ill COVID-19 patients with severe pneumonia - Elabbadi, Alexandre (Infection, 2021)
Severe 2019 novel coronavirus infectious disease (COVID-19) with pneumonia is associated with high rates of admission to the intensive care unit (ICU). Bacterial coinfection has been reported to be rare. We aimed at describing the rate of bacterial coinfection in critically ill adult patients with severe COVID-19 pneumonia. All the patients with laboratory-confirmed severe COVID-19 pneumonia admitted to the ICU of Tenon University-teaching hospital, from February 22 to May 7th, 2020 were included. Respiratory tract specimens were obtained within the first 48 h of ICU admission. During the study period, 101 patients were referred to the ICU for COVID-19 with severe pneumonia. Most patients (n = 83; 82.2%) were intubated and mechanically ventilated on ICU admission. Overall, 20 (19.8%) respiratory tract specimens obtained within the first 48 h. Staphylococcus aureus was the main pathogen identified, accounting for almost half of the early-onset bacterial etiologies. We found a high prevalence of early-onset bacterial coinfection during severe COVID-19 pneumonia, with a high proportion of S. aureus. Our data support the current WHO guidelines for the management of severe COVID-19 patients, in whom antibiotic therapy directed to respiratory pathogens is recommended. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s15010-020-01553-x) contains supplementary material, which is available to authorized users.